Analysis of Low-Income Community Level Models as Determinants of Waste Management, Clean Living Behavior, and Environmental Health in Surabaya City - Febriari Megahayati; Farida Pulansari; Minto Waluyo (PT Mattawang Mediatama Solution, 2023)
As the second largest city in Indonesia, Surabaya deals with various problems, one of which is about poverty. It will lead to other problems, such as environmental problems, especially in the field of environmental health, clean water. The volume of household waste in Surabaya City which reaches 8-9 thousand tons/m3 also exacerbates environmental and environmental health problems. This study aims to analyze the influence of Low-Income Communities (LIC) on Clean Living Behavior (CLB) and Waste Management, the influence of Clean-Living Behavior (CLB) on Environmental Health and the influence of Waste on Environmental Health. This type of research is descriptive quantitative. The source of research data used secondary data obtained from several data sources with a target of 154 urban villages in the Surabaya city. Data collection techniques were carried out using Field Research techniques. The research method employed the AMOS SEM method. The results of the study revealed that Low-Income Communities have a significant influence on the variables of Clean-Living Behavior and Waste in the Surabaya Community. Meanwhile, Clean Living Behavior and Waste do not have a significant influence on Environmental Health variables in the people of Surabaya.